Occupational hazard: Predictors of stress among jail correctional officers - Castle, Tammy L. (American journal of criminal justice, 2006)
The plethora of literature on correctional officers and the work environment, more specifically occupational stress, has focused almost exclusively on officers working in prison facilities. The primary purpose of the current study was to examine the predictors of occupational stress and general stress among 373 jail correctional officers in one state in the Northeast, using the Stressors identified in the previous literature on prison correctional officers and occupational stress. The results indicated that organizational strengths, perceived danger, role problems, and job satisfaction were significant predictors of both occupational and general stress. In addition, gender and salary predicted occupational stress while correctional experience and training predicted general stress. Suggestions are made for administrators, as well as future research on the workplace experiences of correctional officers.